Biomolecule-assisted hydrothermal synthesis of silver bismuth sulfide with nanostructures - Kaowphong S. (2014)
Silver bismuth sulfide (AgBiS 2) nanostructures were successfully prepared via a simple biomolecule-assisted hydrothermal synthesis at 200 °C for 12-72 h. Silver nitrate, bismuth nitrate and l-cysteine were used as starting materials. Here, the biomolecule, l-cysteine, was served as the sulfide source and a complexing agent. The products, characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM), were cubic AgBiS 2 nanoparticles with a diameter range of about 20-75 nm. It was found that their crystallinity and particle size increased with increasing reaction time. The energy dispersive X-ray spectroscopy (EDX) and inductively coupled plasma optical emission spectrophotometry (ICP-OES) analyses were used to confirm the stoichiometry of AgBiS 2. The optical band gap of the AgBiS 2 nanoparticles, calculated from UV-vis spectra, was 3.0 eV which indicated a strong blue shift because of the quantum confinement effect. A possible formation mechanism of the AgBiS 2 nanoparticles was also discussed. © 2011 Elsevier Inc. All rights reserved.